'Something in the way you move': Infants are sensitive to emotions conveyed in action kinematics. Issue 1 (20th June 2019) - Addabbo, Margaret; Vacaru, Stefania V.; Meyer, Marlene; Hunnius, Sabine
Abstract: Body movements, as well as faces, communicate emotions. Research in adults has shown that the perception of action kinematics has a crucial role in understanding others' emotional experiences. Still, little is known about infants' sensitivity to body emotional expressions, since most of the research in infancy focused on faces. While there is some first evidence that infants can recognize emotions conveyed in whole‐body postures, it is still an open question whether they can extract emotional information from action kinematics. We measured electromyographic (EMG) activity over the muscles involved in happy ( zygomaticus major, ZM ), angry ( corrugator supercilii, CS ) and fearful (frontalis, F) facial expressions, while 11‐month‐old infants observed the same action performed with either happy or angry kinematics. Results demonstrate that infants responded to angry and happy kinematics with matching facial reactions. In particular, ZM activity increased while CS activity decreased in response to happy kinematics and vice versa for angry kinematics. Our results show for the first time that infants can rely on kinematic information to pick up on the emotional content of an action. Thus, from very early in life, action kinematics represent a fundamental and powerful source of information in revealing others' emotional state. Abstract : By measuring facial EMG activity we have shown that 11‐month‐old infants are sensitive to emotions conveyed in action kinematics. Evidence for selective facial reactions was found in response to happy (leading to increased zygomaticus major (ZM) activation) and angry (leading to increased corrugator supercilii (CS) activation) action kinematics.